EU Procedural Law Revisited: The Reformed EU Judicial Architecture between the Statute of the Court of Justice and the Rules of Procedure - Lorenzo Grossio; Davor Petrić (European Papers)
(Series Information) European Papers - A Journal on Law and Integration, 2025 10(2), 293-326 | Article | (Table of Contents) 1. Introduction: scope and purposes of the analysis. – 2. The partial transfer of preliminary references from the Court to the General Court. – 2.1. The scope of the General Court’s jurisdiction on preliminary references. – 2.2. The guichet unique mechanism. – 2.3. The procedure for hearing and determining preliminary references at the General Court. – 2.4. The revision of preliminary rulings issued by the General Court. – 3. The new rules on transparency and participation in preliminary reference proceedings. – 4. The extension of the scope of application of the filtering mechanism on appeal. – 5. Not a conclusion but… rather a way forward. | (Abstract) The article provides a critical assessment of the 2024 reform of the Statute of the Court of Justice of the European Union, combining the analysis of the amended provisions of Protocol No 3 and the Rules of Procedure of both the Court of Justice and General Court. To that aim, the contribution takes a procedural standpoint on the topic, with a view to paving the way to the various perspectives featured in the Special Section. Focusing on the transfer of jurisdiction on preliminary references, the article discusses the rationales behind the selection of ‘areas of law’ subject to devolution, thereby disclosing that the reform leaves a ‘variable geometry’ scope to the Court of Justice for being involved in cases in any domain of EU law. That part of the analysis is complemented by assessing the new filing and distributing mechanism for preliminary references (guichet unique), the revision mechanism for preliminary rulings issued by the General Court, and the latter’s new procedural framework for treating preliminary references. While the procedure has been designed in a way to mirror that already applied by the Court of Justice, the article argues that the General Court’s distinctive features may significantly impact the way in which it deals with preliminary references. The analysis then discusses the design and consequences of the new provisions on participation in preliminary references and publication of parties’ written submissions, as well as the rationales and impact of extending the scope of application of the prior admission on appeal mechanism.